2018
DOI: 10.1002/ppap.201700250
|View full text |Cite
|
Sign up to set email alerts
|

White paper on the future of plasma science for optics and glass

Abstract: This paper reflects on the future of low-temperature plasma science in relation to the manufacturing and novel uses of glass. The text summarizes the current state of the art on the major topics discussed, such as glass processing, optics and photonics, healthcare issues, building and fenestration applications. It also identifies several challenges that are driven by applications, and which are compatible with roadmaps for their respective industries. The frontiers of plasma science are discussed, for example,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 312 publications
(316 reference statements)
0
21
0
Order By: Relevance
“…Several methods of surface deposition have been investigated in the pursuit of a reliable BAG coating of DIs, including glazing [177,179,180,181], sol-gel deposition [182,183], electrophoretic deposition [184,185], pulsed laser deposition [186,187], ion-beam [188], and radio-frequency magnetron sputtering [189,190,191]. The radio-frequency magnetron sputtering (RF-MS), which yields a coating with excellent adherence and purity even in complex geometrical objects, seems promising [192,193]. In vivo animal studies of BAG-coated Ti-DIs osseointegrated with significantly more surrounding bone tissue than control DIs [194,195].…”
Section: Clinical Applications Of Bioactive Glasses In Dentistrymentioning
confidence: 99%
“…Several methods of surface deposition have been investigated in the pursuit of a reliable BAG coating of DIs, including glazing [177,179,180,181], sol-gel deposition [182,183], electrophoretic deposition [184,185], pulsed laser deposition [186,187], ion-beam [188], and radio-frequency magnetron sputtering [189,190,191]. The radio-frequency magnetron sputtering (RF-MS), which yields a coating with excellent adherence and purity even in complex geometrical objects, seems promising [192,193]. In vivo animal studies of BAG-coated Ti-DIs osseointegrated with significantly more surrounding bone tissue than control DIs [194,195].…”
Section: Clinical Applications Of Bioactive Glasses In Dentistrymentioning
confidence: 99%
“…Simultaneously, the ionisation probability of the neutral working gas molecules is augmented by several orders of magnitude, having as an effect a more stable plasma and greater number of available bombarding ions, and thus, a significant improvement of the sputtering yield [367]. Furthermore, radio-frequency magnetron sputtering (RF-MS) has a series of other remarkable advantages, including: high purity, excellent adherence, uniformity in both thickness and composition on large-area substrates (dependent only on the magnetron gun size), compactness, ability of facile engineering of film properties by variation of the process parameters (working pressure, electric power, target-to-substrate separation distance, substrate temperature, working gas composition), or the possibility of coating complex-shaped objects if adopting planetary rotation holders [367,368,369]. The demonstrated ability of RF-MS to surpass technological barriers and be scaled up with ease to an industrial level (as shown in the optoelectronics industry) [367,369] should increase its desirability in the biomedical field also.…”
Section: Bioactive Glasses and Glass-ceramicsmentioning
confidence: 99%
“…Continued progress and emerging applications will guarantee an ongoing interest in the further developments of plasma coating and processing methods. Respective challenges and newest developments in the area of optics and glass are described in more detail in a recent “white paper on the future of plasma science for optics and glass.” Since a major limitation of current procedures is the need for operation at reduced pressures, major breakthroughs in the development of atmospheric‐pressure procedures that are providing the same quality and characteristics as low pressure methods are highly desirable and are currently driving major research efforts. Even without this achievement, plasma‐based processes are already competing successfully with wet chemical ones for surface activation and cleaning, and hold the promise to become the gold standard.…”
Section: Fields Of Application For Plasma Technologiesmentioning
confidence: 99%
“…Concurrently, for each of the topics that were discussed during the workshops individual “white papers” were compiled that present more details especially on trends and the different research questions in the respective areas. Four of them have already been published on “the future of plasma science for optics and glass,” “the future of plasma science and technology in plastics and textiles,” “the future of plasma science in environment, for gas conversion and agriculture,” and “plasma for medicine and hygiene.”…”
Section: Introductionmentioning
confidence: 99%